Policy convergence: A conceptual framework based on lessons from renewable energy policies in the EU - Sebastian Strunz; Erik Gawel; Paul Lehmann; Patrik Söderholm (Helmholtz-Zentrum für Umweltforschung (UFZ), 2015)
The literature on policy convergence has identified numerous aspects and possible causal drivers of convergence. We classify and condense these into a comprehensive framework, which is operationalized for support policies for renewable energy sources in the EU. Our analysis advances the conceptual discussion in two ways. First, we demonstrate that conceptual specifications of convergence (e.g., whether to focus on policy targets, instrument design or policy outcomes) rely on normative assumptions. Second, we argue that theories of economic and political convergence processes complement each other: studies of economic convergence are apolitical as they do not aim to explain why states choose or should choose the same policies to solve a given problem. At the same time, economic convergence yields a necessary condition for successful policy convergence. The empirical evidence, in turn, suggests conditional convergence of support policies and renewables shares in the EU, but does not hint at absolute convergence.
Keywords: 330; economic convergence; policy convergence; renewable energy sources; support policies